Reseñas sobre Mertens, D. (2005). Research and Evaluation in Education and Psychology. Integrating Diversity with Quantitative, Qualitative, and Mixed Methods. 2da. ed. Thousand Oaks, CA: SAGE. - Burga León, Andrés Alberto (Revista Peruana de Investigación Educativa, 2009)
Esta es la reseña del libro sobre Mertens, D. (2005). Research and Evaluation in Education and Psychology. Integrating Diversity with Quantitative, Qualitative, and Mixed Methods. 2da. ed. Thousand Oaks, CA: SAGE.